Pengaruh struktur modal, profitabilitas, intellectual capital dan keputusan pendanaan terhadap nilai perusahaan - Seltiana Srykoranti Marut; Abdul Halim; Lilik Sri Hariani (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2020)
This study aims to test the influence of capital structure, profitability, intellectual capital, funding decisions on the value of companies, property and real estate sectors listed on the Indonesia Stock Exchange. The research method uses quantitative methods with multiple linear regression models. Sampling method using purposive sampling,. The variables studied are capital structure, profitability, intellectual capital, funding decisions and the value of the company. The results of this study showed that simultaneously variable capital structure, profitability, intellectual capital and funding decisions have a significant effect on the value of the company with a significant value of F-test of 0.000. While individually (Partial) variable capital structure (DER) profitability (ROA), intellectual capital (VAIC), funding decisions (DAR) have a positive effect on the value of the company (TOBINS Q). This research proves that intellectual capital has a dominant influence on the value of companies with a standardized regression coefficient value of 0.266 greater than other variables that are researched. Researchers should then use other variables that are expected to affect the value of the company such as dividend policy because the increase in dividends gives a positive signal to investors so as to increase the value of the company